2014
DOI: 10.3846/13923730.2014.904813
|View full text |Cite
|
Sign up to set email alerts
|

Complex Assessment Model for Advanced Technology Deployment

Abstract: Abstract. The construction sector constantly offers new products, more effective technologies and novel solutions aimed at improvement of the quality of human habitats and wider distribution of technologies. Currently, effective technologies that require less time and costs for production, installation and use are gaining greater significance. Among them are construction materials and technologies with increasingly popular sustainability features. Considering the above, the article offers a complex algorithm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…Multi-criteria decision making methods are applied for deterministic problem solving, when the set of alternatives are known and are directly determined at the beginning of the selection process: ELECTRE group of methods (ELECTRE I, ELECTRE II, ELECTRE III, ELECTRE IV, ELECTRE A, ELECTRE TRI) (Zavadskas et al 2013;Radziszewska-Zielina 2010) are based on overbalance of the ratio and assigned to overbalance ratio approach methods and should be assigned to grouping and classification group methods according to their purpose; the PROMETHEE group of methods (PRO-METHEE I, II, III and IV) (Kabak, Dağdeviren 2014;Podvezko, Podviezko 2010); and the PCCA procedure, which is the basis, on which these methods are developed: Mappac, Pragma, Cartesian methods (Matarazzo 1990;He et al 2009); AHP method (Esmaeili et al 2014;Rostamzadeh et al 2014;Gudienė et al 2014;Šiožinytė et al 2014;Kildienė et al 2014).…”
Section: Multi-criteria Evaluation Methodsmentioning
confidence: 99%
“…Multi-criteria decision making methods are applied for deterministic problem solving, when the set of alternatives are known and are directly determined at the beginning of the selection process: ELECTRE group of methods (ELECTRE I, ELECTRE II, ELECTRE III, ELECTRE IV, ELECTRE A, ELECTRE TRI) (Zavadskas et al 2013;Radziszewska-Zielina 2010) are based on overbalance of the ratio and assigned to overbalance ratio approach methods and should be assigned to grouping and classification group methods according to their purpose; the PROMETHEE group of methods (PRO-METHEE I, II, III and IV) (Kabak, Dağdeviren 2014;Podvezko, Podviezko 2010); and the PCCA procedure, which is the basis, on which these methods are developed: Mappac, Pragma, Cartesian methods (Matarazzo 1990;He et al 2009); AHP method (Esmaeili et al 2014;Rostamzadeh et al 2014;Gudienė et al 2014;Šiožinytė et al 2014;Kildienė et al 2014).…”
Section: Multi-criteria Evaluation Methodsmentioning
confidence: 99%
“…Waris et al [25] identified some important criteria for selection of sustainable on-site construction equipment based on the fundamental concept of sustainability and provided an assessment framework to guide the decision makers for appraising the selection process. Kildienė et al [26] designed a multi-criteria assessment model based on AHP and permutation methods to assess the deployment and distribution potential of a new technology/product for construction sector. Mital et al [27] developed a modeling framework to design material handling system and warehouses under uncertainty to maximize the efficiency of the system while minimizing the risk of implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At individual stages of the lifecycle of an undertaking, analysed phenomena are very complex, which is mainly due to specific traits, characteristics, complexity and nature of construction processes and relations between them. On the other hand, a description of these relations is based mainly on expert opinions and should take into account both measurable factors and those difficult to measure (Ustinovichius et al 2006;Kildienė et al 2014;Vodopivec et al 2014); besides, its quality depends largely on expert knowledge and experience of decision-makers.…”
Section: Introductionmentioning
confidence: 99%